Academic Attitude as Mediator between the Relationship of Blended Learning Environment and Student’s Performance in Technology and Livelihood Education - Donna Bella Clavero; Edna O. Briones (MASI Mandiri Edukasi, 2023)
The onset of the new normal in the school, as an effect of the COVID-19 pandemic, highlighted the importance of using blended learning to embrace the transition from pure online to face-to-face classes. This study intends to ascertain the mediating influence of academic attitude on domestic factors, teaching-learning practices, and students' performance in TLE (Technology and Livelihood Education) - Cookery in a Blended Learning environment among the Grade 9 students of St. John of Beverly School Inc. and the challenges of the new normal setup in education. The study employed the descriptive correlational design and a survey questionnaire distributed via Google Forms-Pearson product-moment-correlation coefficient to determine the relationship among the variables. The results revealed that academic attitude, self-discipline, and motivation have a significant effect on cognitive performance with r = .337 and r =.318 significance when tested at a .05 level of significance, respectively, and self-discipline has a significant effect on psychomotor performance with r =.282 significance when tested at a 0.05 level of significance. The researcher, however, recommends further study to investigate other academic attitudes such as optimism, diligence, perseverance, and resourcefulness or other more appropriate variables to study the mediating role of academic attitudes in the blended learning environment on students’ cognitive and psychomotor performance.